TELAAH RETURN SAHAM BANK DI INDONESIA BERBASIS INDIKATOR KINERJA KESEHATAN KEUANGAN BANK - Maharani, Alin Sastiti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
Abstract: The objectives of this research are to determine whether the ratioCAELS affects the stock returns and whether the stock returns of government banks are better than stock returns of private banks. This research used secondary data generated from audited financial statements from 2010 to 2012.The sample consisted of 16 banks. Results of the t-tests showed that not all of the variables used in this study influenced the stock returns.Stock returns of government banks in 2010, 2011, and 2012 were higher than the private bank stock returns. Keywords: CAELS Ratios, Stock Returns, Financial Statements